IDDF2020-ABS-0045 Clinical significance of intra-abdominal pressure measurement in patients with acute abdomen requiring exploratory laparotomy. (18th November 2020) - Goswami, Binita; Pathania, Sumit; Gupta, Arun K; Gupta, Nikhil
Abstract : Background: Intra-abdominal Hypertension (IAH) has been identified as a significant risk factor for morbidity and mortality. Our study was done to monitor intra-abdominal pressure (IAP) in patients with acute abdomen requiring exploratory laparotomy and to determine its effect on multiple organs by measuring SOFA score and its effect on the outcome of patients. Methods: It was an observational study in which IAP was measured pre and post-operatively by inserting a catheter in the urinary bladder using manometer 6 hourly in patients of acute abdomen requiring exploratory laparotomy. Results: Of 60 patients 23 (38%) had IAP (mean) and 24 (40%) had IAP (max) more than 12 mmHg. Patients with intestinal obstruction and intestinal perforation with peritonitis had an incidence of raised IAP. There was an increase in hospital stay in patients with IAH, and this was statistically significant (p <0.05). There was positive correlation coefficient relationship between IAP (mean) and (max) with hospital stay r IAP (max) =0.4757 and r IAP(max) =0.4893. Elevated IAP affects all organs, but cardiovascular, renal and respiratory systems were more prone to failure, and there was a positive correlation between IAP and organ failure. Conclusions: IAP should be routinely measured in patients of acute abdomen requiring exploratory laparotomy. Patients with raised IAP preoperatively should be taken up for emergency surgery as soon as possible for a better outcome before deleterious effects of raised IAP on various organ system set in.